PENGARUH SKEPTISISME PROFESSIONAL DAN KOMPETENSI AUDITOR TERHADAP JUMLAH TEMUAN AUDIT - Herawati, Hetti; Lubis, Yeni Rewinda (Universitas Pendidikan Indonesia, 2015)
Abstract. The purpose of this research is to know the influence of Professional Skepticism and competence of Auditors Against the number of Audit Findings the audit process in carrying out both partially or simultaneous. The object of the research is a public accountant in North Bandung area.Â The method in this research is descriptive causal, and acquisition of data is done with the dissemination of the questionnaire. In analyzing the data used multiple regression. The hypothesis in this study: